The Impact of Transformational Leadership on Job Satisfaction and Employee Performance (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study aimed to analyze the effect of transformational leadership on job satisfaction and employee performance. This was a quantitative study. The data were analyzed using the SPSS Ver. 25. This study involved employees of the Northern Technical University in Iraq, who were taken using proportional random sampling techniques so that 125 employees were selected as research respondents. The results of the study showed that transformational leadership has a positive and significant effect on employee performance and job satisfaction the practical implications of these findings underscored the importance of developing transformational leadership as strategies for improving employee performance in public organizational environments. These implications could help organizations design more effective human resource development policies and programs.
Keywords: Transformational Leadership; Job Satisfaction; Employee Performance; Northern Technical University; Human Resources Management; Employees